(untitled) (Terr@ Plural, 2021)
This study aims to evaluate the vulnerability of groundwater to contamination in the Urubu river watershed, Tocantins. The analysis was based on the VIX vulnerability index and considered the areas with the highest water accumulation, as indicated by the NDWI index values ​​extracted from the study area. It was observed that the highest values ​​of the VIX index were found in areas in which the groundwater levels were deeper. The western region of the basin presented areas more vulnerable to contamination due to the shallow depth of the water table. The use of the VIX and NDWI indices was effective in determining areas that are more susceptible to contamination within the Urubu river basin, thus, it can be considered an efficient tool for local natural resource management. Key-words: Groundwater, VIX index, NDWI, Vulnerability, Urubu river.